2018
DOI: 10.1186/s12995-018-0220-y
|View full text |Cite
|
Sign up to set email alerts
|

The office work and stretch training (OST) study: an individualized and standardized approach for reducing musculoskeletal disorders in office workers

Abstract: BackgroundMusculoskeletal disorders (MSD) are a common health problem in office workers. In Germany, MSD (mainly back pain related) are the main cause of workdays lost to incapacity. This is not only bothersome for the employees, but also causes higher costs for the health system and employers. Workplace health promotion programmes (WHPP) can help to reduce this as they reach large target groups and are easily accessible. In this context, stretch training exercises have already proven to be effective. In the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 72 publications
1
26
0
2
Order By: Relevance
“…Not only in Germany, but also in other industrial countries [1,2], studies on musculoskeletal disorders (MSD) have been conducted in various occupational sectors [3][4][5][6][7][8][9][10], for example, in the health sector [11][12][13]. In this sector, a high prevalence of musculoskeletal pain in the neck, shoulder and lower back region is observed [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Not only in Germany, but also in other industrial countries [1,2], studies on musculoskeletal disorders (MSD) have been conducted in various occupational sectors [3][4][5][6][7][8][9][10], for example, in the health sector [11][12][13]. In this sector, a high prevalence of musculoskeletal pain in the neck, shoulder and lower back region is observed [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Myers laid the foundations for myofascial chains in 1997, while Stecco in 1988 saw muscle continuity and acupuncture meridians [22][23]. The concept of myofascial chains, that is, the tension of a contractile district has repercussions and influences other districts near and far, is used in different disciplines, from physiotherapy to yoga, from sport to meditation (Figure 4) [24][25][26][27][28]. Photo was given by Dr Anthony Chrisco.…”
Section: Fascial Models: Myofascial Chainsmentioning
confidence: 99%
“…The authors showed mostly adequate intra- and inter-rater reliability as well as validity for smartphone devices on all joints assessed. However, the intra-rater reliability of the DI has been shown to be equivalent [ 9 ] to the goniometer, while the inter-rater reliability was found to be superior [ 10 , 11 ], since the exact placement of goniometer can be difficult [ 7 , 12 , 13 ]. The reliabilities of the DI and TM procedures, however, do differ [ 2 , 14 ]; for example, in evaluating the flexion of the lumbar spine reliability was found to be inconsistent for several (slightly) modified versions of the Schoeber method using a TM [ 15 – 17 ] and an inclinometer placed on the spine [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%